ARCASIA architectural timeline chart : Malaysia - Mohd Nawawi, Norwina; Abdul Jamal, Hamdan; Chan, Hean Kee (Humanities Press, 2006)
This book is a project by the ARCASIA Committee for Architectural Education (ACAE), contributed by 17 Institute of Architects in ASIA i.e. Bangladesh, China, Hong Kong, India,Indonesia, Japan, Korea, Macau,Malaysia, Mongolia,Nepal, Pakistan,Philippines, Singapore,Sri Lanka, Thailand, Vietnam. Each institute of the country contribute 2 pages of pictorial time line of the country's architecture with write up of the its history in summary.